2022
DOI: 10.1186/s40463-022-00580-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving predictability of IgE-high type 2 chronic sinusitis with nasal polyps in the biologic era

Abstract: Background Chronic rhinosinusitis (CRS) is an inflammatory disease that may require biological therapy. Omalizumab is an anti-IgE biologic that was recently approved by the FDA and Health Canada for use in severe CRS with nasal polyps (CRSwNP) recalcitrant to intranasal corticosteroids. Dosing is based on weight and pre-treatment serum IgE, with elevated levels of the latter being an indication for biologic treatment according to EPOS and EUFOREA guidelines. The goal of this study was to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…There was limited evidence for CRSsNP ( n = 1) and asthma in this review, so it is difficult to confidently discern the impact of nasal polyposis on non‐type 2 inflammation. It is possible that nasal polyposis plays a predictive role when placed in a model consisting of multiple variables 30,45 . Interestingly, being in Taiwan may have influenced this study's type 3 endotype shift, as Staudacher 44 demonstrated a higher proportion of type 3 inflammation in patients from Beijing when compared with Europe, Australia, and the United States 44 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There was limited evidence for CRSsNP ( n = 1) and asthma in this review, so it is difficult to confidently discern the impact of nasal polyposis on non‐type 2 inflammation. It is possible that nasal polyposis plays a predictive role when placed in a model consisting of multiple variables 30,45 . Interestingly, being in Taiwan may have influenced this study's type 3 endotype shift, as Staudacher 44 demonstrated a higher proportion of type 3 inflammation in patients from Beijing when compared with Europe, Australia, and the United States 44 …”
Section: Discussionmentioning
confidence: 92%
“…It is possible that nasal polyposis plays a predictive role when placed in a model consisting of multiple variables. 30,45 Interestingly, being in Taiwan may have influenced this study's type 3 endotype shift, as Staudacher 44 demonstrated a higher proportion of type 3 inflammation in patients from Beijing when compared with Europe, Australia, and the United States. 44 In patients that had a mixed endotype shift, there is likely a unique unified airway inflammatory mechanism due to Håkansson et al 29 demonstrating an association between nasal polyp and bronchial type 1 and 2 inflammatory cytokines.…”
Section: Endotypes In Comorbid Chronic Rhinosinusitis and Asthmamentioning
confidence: 97%
“…Similarly, most respondents are aware of the importance of IgE in defining type 2 inflammation as suggested by the literature 15 , 16 , even if less than half of patients have total blood IgE routinely measured. In fact, most respondents (82%) agree that measuring total IgE is useful to define type 2 inflammation (Q14 s.f.…”
Section: Results and Practical Recommendationsmentioning
confidence: 99%
“…Regarding the use of follow-up CBCs during biologic treatment for CRSwNP, almost half (45%) of the respondents perform these tests every 3 months, over a third perform them bi-monthly or monthly (15% and 22%), and fewer (15%) perform them every 6 months (Q12 s.f.). Similarly, most respondents are aware of the importance of IgE in defining type 2 inflammation as suggested by the literature 15,16 , even if less than half of patients have total blood IgE routinely measured. In fact, most respondents (82%) agree that measuring total IgE is useful to define type 2 inflammation (Q14 s.f.…”
Section: Defining Type 2 Inflammation In Biologic Therapy Candidates ...mentioning
confidence: 99%
See 1 more Smart Citation